Amyotrophic Lateral Sclerosis: The Most Common And Lethal Form Of Motor Neuron Disease-a Case Report From Middle East - Waseem Mehmood Nizamani; Ameet Jesrani; Mujtaba Khan; Kalthoum Tlili; Nader Al Khuraish; Kashaf Anwar Arain (Journal of Bahria University Medical and Dental College)
A neurodegenerative disorder which is fatal, rapidly progressive and has no effective treatment till date is amyotrophic lateral sclerosis. Almost 90% of all cases occur in the sporadic form, with the rest occurring in the familial form. It is a devastating disease leading to death within 3-5 years in most cases. The diagnosis of AML is difficult to made in spite of acknowledgment for 140 years. It is diagnosed by clinical presentation which is a combination of upper and lower motor neuron signs and electro diagnostic studies which gives information about diffuse motor axonal injury. This neurodegenerative disorder results in degeneration of corticospinal tracts and anterior horn cells and involving motor neurons of the cerebral cortex, brainstem, and spinal cord. There are a variable signs and symptoms of this disease, so the diagnosis is very important for the management and better outcome of the patients. Cause of death in these patients is usually respiratory failure.